Espduino-32 Utilization in the Warehouse Storage Information System of the Metal Processing Industry Department - Miranty Miranty; Andy Nasriadi (Politeknik STMI Jakarta, 2024)
An information technology system basically includes 3 things, namely hardware such as computers and printers, then software, and also the user or user who controls it, or what is usually called brainware. In the industrial world, information systems are needed to facilitate the work carried out by users. Based on the results of observations at the research location, several problems were found, namely the process of searching for items took a long time due to the location of the items not being well organized and the layout of the shelves in the warehouse being quite confusing. The number of items in the warehouse is also not recorded, making the warehouse manager unable to confirm the number of items in the warehouse. Numbering shelves in the warehouse is also a problem because insufficient lighting makes it difficult for users to find the right shelf in a short time. By designing an information system in the form of a website related to the warehouse inventory system which is connected using WiFi connectivity with the Espduino-32 module which controls the relay to turn on the shelf marker lights when and during the user's search for items. The results obtained from the implementation are that the process of searching for items in the warehouse is easier and can be done in a short time with the shelf number information listed in the search system as well as the indicator lights that will light up during the search process